Water diversion in Brazil threatens biodiversity - Daga, Vanessa S. (2020)
Construction of water diversions is a common response to the increasing demands for freshwater, often resulting in benefits to communities but with the risk of multiple environmental, economic, and social impacts. Water-diversion projects can favor massive introductions and accelerate biotic homogenization. This study provides empirical evidence on the consequences of a proposed law intended to divert water from two large and historically isolated river basins in Brazil: Tocantins to Sao Francisco. Compositional similarity (CS) and beta-diversity were quantified encompassing aquatic organisms: mollusks, zooplankton, crustaceans, insects, fishes, amphibians, reptiles, mammals, and plants. For CS we (i) considered only native species, and (ii) simulated the introduction of non-natives and assumed the extinction of threatened species due to this water-diversion project. We highlight the environmental risks of such large-scale projects, which are expected to cause impacts on biodiversity linked to bioinvasion and homogenization, and we recommend alternatives in order to solve water-demand conflicts.